Diseño de una planta de tratamiento de aguas residuales del centro de acopio de leche COPROCACB, Parroquia Quimiag - Asitimbay Ilbay, Jonathan Fernando (2023)
In the dairy industry, water is a fundamental part of its processes, which when discharged without any type of treatment these waters with pollutant loads directly affect the environment, therefore, the present research project entitled Design of a wastewater treatment plant for the COPROCACB milk collection center of the Quimiag parish in the Riobamba canto of the Province of Chimborazo, where a methodology was applied in which the problem caused by the discharge of wastewater from the process of washing tanks and equipment used in the collection center was determined in situ, where a methodology was applied in which the problem caused by the discharge of wastewater from the process of washing tanks and equipment used in the collection center was known in situ, in the same way a flow rate of 2.30 L/s was determined for the selection and design of the treatment units, together with the analyses obtained in the physical-chemical and microbiological characterization of the wastewater, so that the results reflect the parameters that are not within the range established in the environmental quality and effluent water discharge standards, The treatment plant will consist of a homogenizing tank, a grease trap, a primary sedimenter, a DAF aeration system and finally an anaerobic biodigester U. A. S. B. Finally, the treatment plant will be equipped with an anaerobic biodigester U. A. S. B., which will be used to treat the wastewater from the collection center. A.S.B. Finally, the effectiveness is determined by the percentage of elimination of the treatment units which guarantee a treated water that will be in the optimal ranges of the regulations for effluent discharges.